A arquitetura do problema: o potencial criativo no exercício de projeto - Lanna Larissa Rodrigues Rêgo de Oliveira (2017)
Starting from the understanding of the need for a teacher training in architecture project teaching that prioritizes the development of the creative potential of students, this research was based on the updates of the cognitive sciences, mainly in neuroscience, adopted for offering scientific bases that allow to identify the assumptions of stimulus to human creative activity in order to elucidate attributes by which this potential can be stimulated in students. For this, we systematize the possible nature of the tasks, according to which we are pushed to a greater or lesser degree to solve them creatively and later we analyze these different natures from the perspective of possible design problems in educational contexts of architecture, indicating that the nature of the design problems, because it is complex, denotes a high potential for creative student development, as long as the problem proposed to the student does not provide excessive levels of pre-determinations. Allied to this, the development of a discipline in the context of the disciplines of architectural design of Flexible Projects PFlex at UFMG, was observed analytically and critically, in order to complement with my reflections as a masters degree, to lay the foundations for the development of guidelines of a disciplinary exercise that contemplates the prerogative of a project problem more open to the discussion, interaction and critical proposition of the students. Finally, we developed an empirical application of the guidelines that we systematize from the previous steps, as a disciplinary experiment in the PFlex at UFMG. Analyzing the results, limits and potentials achieved, we conclude positive the experience of teacher initiation through research, since it allows replication, adaptation and re-evaluation by other professionals and researchers in the initial phase of teacher education in architecture, contributing to the advancement of architectural teaching practice.